Later midline shift is associated with better post-hospitalization discharge status after large middle cerebral artery stroke - Song, Jonathan J.; Stafford, Rebecca A.; Pohlmann, Jack E.; Kim, Ivy So Yeon; Cheekati, Maanyatha; Dennison, Sydney; Brush, Benjamin; Chatzidakis, Stefanos; Huang, Qiuxi; Smirnakis, Stelios M.; Gilmore, Emily J.; Mohammed, Shariq; et al. (Scientific reports, 2025)
Space occupying cerebral edema is a feared complication after large ischemic stroke, occurring in up to 30% of patients with middle cerebral artery (MCA) occlusion and peaking 2–4 days after injury. Little is known about the factors and outcomes associated with peak edema timing, especially after 96 h. We aimed to characterize differences and compare discharge status between patients who experienced maximum midline shift (MLS) or decompressive hemicraniectomy (DHC) in the acute (< 48 h), average (48–96 h), and subacute (> 96 h) groups. We performed a two-center, retrospective study of patients with ≥ 1/2 MCA territory infarct and MLS. We constructed a multivariable model to test the association of subacute peak edema and favorable discharge status, adjusting for various confounders. Of 321 eligible patients, 32%, 36%, and 32% experienced acute, average, and subacute peak edema. Subacute peak edema was significantly associated with higher odds of favorable discharge than acute peak edema (aOR, 2.05; 95% CI, 1.03–4.11). Subacute peak edema after large MCA stroke is associated with better discharge status compared to acute peak edema courses. Understanding how the timing of cerebral edema affects risk of unfavorable discharge has important implications for treatment decisions and prognostication.